2011
DOI: 10.1673/031.011.7501
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyte Responses of the Colorado Potato Beetle,Leptinotarsa decemlineata, and the Greater Wax Moth,Galleria mellonella, to the Entomopathogenic Nematodes,Steinernema feltiaeandHeterorhabditis bacteriophora

Abstract: Hemocyte encapsulation reactions of infective juveniles of two Iranian isolates of the entomopathogenic nematodes, Heterorhabditis bacteriophora Poinar (Rhabditina: Heterorhabditidae) and Steinernema feltiae Filipjev (Tylenchina: Steinernematidae), were compared in the economic pest Colorado potato beetle, Leptinotarsa decemlineata Say (Coleoptera: Chrysomelidae), and the greater wax moth, Galleria mellonella L. (Lepidoptera: Pyralidae). The former was a more responsive host than the latter and the hemocyte re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Melanization is a cellular immune response of arthropods that results in melanin production at the wound site and that contributes to pathogen killing and wound healing (11,50). Previous studies have shown that EPN infection of some insects results in rapid melanization and encapsulation of IJs although in permissive hosts IJs can escape the capsule and kill the insect (51)(52)(53). Both Xenorhabdus and Photorhabdus produce specific inhibitors of phospholipase A 2 , a key component of the melanization and encapsulation reactions, suggesting that the bacterial endosymbionts of EPNs promote nematode survival by suppressing these reactions (54,55).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanization is a cellular immune response of arthropods that results in melanin production at the wound site and that contributes to pathogen killing and wound healing (11,50). Previous studies have shown that EPN infection of some insects results in rapid melanization and encapsulation of IJs although in permissive hosts IJs can escape the capsule and kill the insect (51)(52)(53). Both Xenorhabdus and Photorhabdus produce specific inhibitors of phospholipase A 2 , a key component of the melanization and encapsulation reactions, suggesting that the bacterial endosymbionts of EPNs promote nematode survival by suppressing these reactions (54,55).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of larger insects, such as the Japanese beetle Popillia japonica, the house cricket Acheta domesticus, and the Colorado potato beetle Leptinotarsa decemlineata, have suggested that differences in virulence among EPNs can be attributed to differences in the abilities of EPNs to infect different hosts as well as differences in the host immune response to infection (51)(52)(53). To investigate the cause of differences in survival rates among Drosophila species exposed to different EPNs, we examined infection rates and postinfection survival rates of selected Drosophila-EPN combinations.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular encapsulation of the EPNs has been reported in CPB (Armer et al, 2004;Ebrahimi, Niknam, & Dunphy, 2011;Ebrahimi, Niknam, & Lewis, 2011;Thurston et al, 1994) and, in part may decrease THC. Plasmatocytes and granulocytes are the main haemocytes involved in encapsulation response of the insects against EPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular encapsulation of EPNs as an immune response of different insect species has been well documented and different interactions of the bacterial, nematode and host genotypes are responsible for variable efficacy of this immune reaction (Li, Cowles, Cowles, Gaugler, & CoxFoster, 2007;Walter, Dunphy, & Mandato, 2008;Wang, Campbell, & Gaugler, 1995;Wang, Gaugler, & Cui, 1994). CPB larvae also have efficient immune responses against EPNs in which melanisation and cellular encapsulation are described (Armer, Rao, & Berry, 2004;Ebrahimi, Niknam, & Dunphy, 2011;Ebrahimi, Niknam, & Lewis, 2011;Thurston, Yule, & Dunphy, 1994). Prophenoloxidases (proPO) are the inactive form of phenoloxidases (PO) and are synthesised primarily by haemocytes, then released into plasma by cell lysis (Kanost & Gorman, 2008).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation